Can AI (Artificial Intelligence) Replace the Role of Accountants? - Wafa, Zaenal; Airawaty, Diana; As'ari, Hasim (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
With an emphasis on information system quality, information quality, and self-efficacy, this study investigates how accounting professionals and students perceive the function and effects of artificial intelligence (AI) in the accounting field. Data was gathered using a combination of methods, including questionnaires and in-depth interviews with a range of stakeholders, such as banking analysts, financial managers, and auditors. Multiple regression analysis shows that system and information quality have a significant impact on user satisfaction while self-efficacy does not.  User satisfaction is the primary factor influencing the use of AI.  Qualitatively, AI is believed to be useful for routine tasks, but its application to challenging decisions is restricted, and it faces challenges pertaining to technical, financial, and human resource readiness.  These results highlight the significance of human-AI cooperation, efficient training methods, and the moral application of digital transformation in accounting.